Facile microwave-assisted hydrothermal synthesis of hexagonal sodium tungsten bronze and its high response to NO2 - Martins, Tiago A.; Machado, Thales R.; Ferrer, Mateus M.; Zanetti, Sonia M. [UNESP]; Longo, Elson [UNESP] (Elsevier, 2016)
Single-phase hexagonal sodium tungsten bronze (h-NaxWO3+x/2·yH2O) was synthesized via a microwave-assisted hydrothermal method. A reaction time of 4 min was sufficient to obtain well-crystallized nanoplates with a thickness of 5–16 nm and length of 5–500 nm. The structure, morphology, and composition of the obtained material were characterized by X-ray diffraction and scanning electron microscopy. H2O molecules and Na species were detected in the hexagonal channels of the tungsten bronze structure. The gas sensing properties were also measured, suggesting that h-NaxWO3+x/2·yH2O can be a promising material for NO2 detection due to the high response observed.
Keywords: Gas sensor; Microwave-assisted hydrothermal method; Nanoplates; Sodium tungsten bronze